PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP AGRESIVITAS PAJAK - Sanjaya, Claudius Fredericko; Ngadiman, Ngadiman (Jurnal Paradigma Akuntansi, 2025)
Based on the research objective to show the influence and interaction between leverage, profitability, and liquidity on the level of tax aggressiveness of industrial companies. In this case, the goods industry in the beverage and food sector has been registered in the range of 2019 to 2021 on the list of the Indonesian Stock Exchange (IDX). The research samples involved were 14 companies with a purposive sampling method of data collection. The data obtained was processed using SPSS software with multiple regression analysis as well as Microsoft Excel 2016. This research shows that there is a significant relationship between profitability and tax aggressiveness. In addition, it also produces leverage and liquidity data that does not have implications for tax aggressiveness.